Elucidating the role of free polycations in gene knockdown by siRNA polyplexes. (15th April 2016) - Klauber, Thomas C.B.; Søndergaard, Rikke V.; Sawant, Rupa R.; Torchilin, Vladimir P.; Andresen, Thomas L.
Graphical abstract: Abstract: Future improvements of non-viral vectors for siRNA delivery require better understanding of intracellular processing and vector interactions with target cells. Here, we have compared the siRNA delivery properties of a lipid derivative of bPEI 1.8 kDa (DOPE-PEI) with branched polyethyleneimine (bPEI) with average molecular weights of 1.8 kDa (bPEI 1.8 kDa) and 25 kDa (bPEI 25 kDa). We find mechanistic differences between the DOPE-PEI conjugate and bPEI regarding siRNA condensation and intracellular processing. bPEI 1.8 kDa and bPEI 25 kDa have similar properties with respect to condensation capability, but are very different regarding siRNA decondensation, cellular internalization and induction of reporter gene knockdown. Lipid conjugation of bPEI 1.8 kDa improves the siRNA delivery properties, but with markedly different formulation requirements and mechanisms of action compared to conventional PEIs. Interestingly, strong knockdown using bPEI 25 kDa is dependent on the presence of a free vector fraction which does not increase siRNA uptake. Finally, we have investigated the effect on lysosomal pH induced by these vectors to elucidate the differences in the proton sponge effect between lipid conjugated PEI and conventional PEI: Neither DOPE-PEI nor bPEI 25 kDa affected lysosomal pH as a function of time, underlining that the possible proton sponge effect is not associated with changes in lysosomal pH. Statement of Significance: Gene silencing therapy has the potential to treat diseases which are beyond the reach of current small molecule-based medicines. However, delivery of the small interfering RNAs (siRNAs) remains a bottleneck to clinical implementation, and the development of safe and efficient delivery systems would be one of the most important achievements in medicine today. A major reason for the lack of progress is insufficient understanding of cell–polyplex interaction. We investigate siRNA delivery using polyethyleneimine (PEI) based vectors and examine how crucial formulation parameters determine the challenges associated with PEI as a delivery vector. We further evaluate how lipid conjugation of PEI influences formulation, cytotoxicity and polymer interaction with cells and cargo as well as the proton sponge capabilities of the vectors.